2017
DOI: 10.3390/cosmetics4010004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Ageing: The Influence of Environmental Pollution, Sunlight and Diet on Skin

Abstract: Skin ageing is a complex process that is determined by both intrinsic and extrinsic factors, which leads to a progressive loss of structure and function. There is extensive evidence indicating that oxidative stress induced by reactive oxygen species plays an important role in the process of human skin ageing. Mitochondria are the major source of cellular oxidative stress and are widely implicated in cutaneous ageing. Extrinsic skin ageing is driven to a large extent by environmental factors and external stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 55 publications
0
51
0
Order By: Relevance
“…Mitochondrial DNA damage leads to further mitochondrial dysfunction and ROS production (increasing oxidative stress within the cell) leading to a putative cycle of ROS production and associated mitochondrial damage . mtDNA damage has been implicated in the aging process in several organs, especially the skin, and mtDNA as a biomarker of damage has been previously demonstrated to reliably and sensitively detect UV‐induced cellular damage . Furthermore, nuclear DNA (nDNA) acts as a chromophore primarily for ultraviolet B (UVB, 290‐320 nm) leading to increased photoproducts and nDNA (as well as mtDNA) is damaged indirectly by longer wavelength ultraviolet A (UVA, 320‐400 nm) induced ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA damage leads to further mitochondrial dysfunction and ROS production (increasing oxidative stress within the cell) leading to a putative cycle of ROS production and associated mitochondrial damage . mtDNA damage has been implicated in the aging process in several organs, especially the skin, and mtDNA as a biomarker of damage has been previously demonstrated to reliably and sensitively detect UV‐induced cellular damage . Furthermore, nuclear DNA (nDNA) acts as a chromophore primarily for ultraviolet B (UVB, 290‐320 nm) leading to increased photoproducts and nDNA (as well as mtDNA) is damaged indirectly by longer wavelength ultraviolet A (UVA, 320‐400 nm) induced ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental pollution is increasing, especially in industrialized countries, and represents a worldwide problem that cannot be passively avoided [31]. Less research has been performed to date on environmental pollutants and human skin aging.…”
Section: Air and Water Pollution And The Generation Of Rosmentioning
confidence: 99%
“…In reference to human skin aging, journal reports have shown that airborne pollutant exposure is correlated with extrinsic skin aging in adults and children [22,31,39]. However, air pollution represents either indoor or outdoor environmental exposure to any chemical, physical, or biological agent.…”
Section: Air and Water Pollution And The Generation Of Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the interaction with nuclear and mitochondrial nucleic acids results in mutations that predispose them to strand breaks [78]. Extrinsic skin aging is generally influenced by environmental factors and external stressors such as UV radiation, pollution and lifestyle factors that stimulate the ROS production and oxidative stress [79].…”
Section: Pollution and Its Effect On The Skinmentioning
confidence: 99%